Reflective imaging, on-axis laser heating and radiospectrometry of samples in diamond anvil cells with a parabolic mirror. Issue 2 (3rd April 2021) - Spiekermann, Georg; Libon, Lélia; Albers, Christian; Sakrowski, Robin; Petitgirard, Sylvain; Sahle, Christoph J.; Sundermann, Martin; Gretarsson, Hlynur; Sergueev, Ilya; Sternemann, Christian; Wilke, Max; Murakami, Motohiko
ABSTRACT: We describe the use of a silver-coated 90 ∘ parabolic mirror of 33 mm focal length as objective for imaging, on-axis laser heating and radiospectrometric temperature measurements of a sample compressed in a diamond anvil cell in a laser heating system. There, spatial resolution and imaging quality of the parabolic mirror are similar to the one of a 10× objective. The temperature measurements between 500 and 900 nm are essentially free from chromatic aberration. The parabolic mirror was also perforated with a 220-μm hole, allowing for on-axis imaging, laser heating and incidence of X-rays simultaneously at synchrotron facilities. The parabolic mirror is thus a well-suited alternative to existing refractive and reflective objectives in laboratory and synchrotron laser heating systems.